The role of BDNF on food intake and overweight: Linking neuroplasticity and obesity - Sequeira Cordero, Andrey (2025)
Overweight and obesity are escalating global health issues significantly driven by poor diet quality and energy balance alterations. The typical Western diet, rich in saturated fats, refined sugars, and salt, not only increases calorie intake but also modifies eating behaviors. Among many neurobiological factors, brain-derived neurotrophic factor (BDNF) has emerged as a crucial modulator of these behaviors. BDNF controls neural development, neurogenesis, synaptogenesis, neuroprotection, survival, and neural signaling. Its role in eating behaviors is complex as it exerts different and sometimes opposing effects depending on the form (i.e., mature BDNF, pro-BDNF, and its pro-domain part) and the brain region involved. This review provides an integrated view of how BDNF relates to food intake and obesity along three main lines. Firstly, exposure to rewarding food triggers BDNF expression/release in the hypothalamus, reducing appetite and achieving satiety. Secondly, BDNF's expression/release within the reward system -e.g., the ventral tegmental area, nucleus accumbens, and dorsal striatum- modulates food-induced motivational/hedonic responses. Thirdly, BDNF in the prefrontal cortex and the hippocampus influences executive functions, learning, and memory processes, modifying decision-making about and behavioral responses to food and its related cues. However, repeated exposure to highly palatable foods induces long-term changes in BDNF expression/release, which along with alterations in other neurobiological factors, may change appetite patterns and hedonic responses. These changes could result in an increase of hunger and food craving leading to overeating and weight gain. This panorama positions BDNF at the forefront in the field of nutrition and related disciplines in the study of obesity.